Pareto improving taxation in incomplete markets - Sergio Turner (Brown University, Department of Economics, 2006)
Focusing on tax policy with incomplete asset markets, we create a framework for proving the existence of Pareto improving taxes, for computing them, and for bounding the improvement. The protagonist is the price adjustment following an intervention. If the price adjustment is sufficiently sensitive to risk aversions, then generically in economies equilibria admit Pareto improving tax rates–if tax parameters and incompleteness exceed household heterogeneity, and multiple commodities exist. We explain how to verify this sensitivity test with standard demand theory. We then illustrate that different policies generically admit Pareto improving taxes, by showing they all pass this sensitivity test. These include (a) taxes on asset purchases, (b) lump-sum taxes on present income plus one flat tax on asset purchases, (c) asset measurable taxes on capital gains, (d) excise taxes on current commodities.
Keywords: D52; D61; E62; 330; Pareto improvement; Slutsky; taxation; incomplete; generic; Steuerpolitik; Mikroökonomische Konsumfunktion; Unvollkommener Markt; Slutsky Gleichung; Theorie